2013
DOI: 10.1021/cm402879r
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition Functionalized Composite SOFC Cathode La0.6Sr0.4Fe0.8Co0.2O3-δ -Gd0.2Ce0.8O1.9: Enhanced Long-Term Stability

Abstract: We report that the long-term stability of a conventional mixed oxide-ion and electron conducting solid oxide fuel cell cathode, La 0.6 Sr 0.4 Fe 0.8 Co 0.2 O 3−δ -Gd 0.2 Ce 0.8 O 1.9 (LSCF-GDC) composite, can be markedly improved by functionalizing its surfaces with a conformal layer of nanoscale ZrO 2 films through atomic layer deposition (ALD). Over a >1100 h testing at 800 °C, the overcoated LSCF-GDC cathode exhibited respective polarization and ohmic area-specific-resistances 3 and 1.5 times lower than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 49 publications
(74 reference statements)
2
41
2
Order By: Relevance
“…As pointed out in the Introduction, two previous studies reported uniform deposition of porous ZrO 2 films in porous electrodes, with growth rates of roughly 0.6 nm/cycle. 4,5 In contrast, growth rates in our work were more than 20 times lower and the large effect of ALD modification on the electrode impedances in our work implies the films must be reasonably dense.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…As pointed out in the Introduction, two previous studies reported uniform deposition of porous ZrO 2 films in porous electrodes, with growth rates of roughly 0.6 nm/cycle. 4,5 In contrast, growth rates in our work were more than 20 times lower and the large effect of ALD modification on the electrode impedances in our work implies the films must be reasonably dense.…”
Section: Discussioncontrasting
confidence: 72%
“…The precursors used in the present study were tetrakis (2,2,6,6-tetramethyl-3,5-heptanedionato) zirconium (Zr(TMHD) 4 , Strem Chemical, Inc.), tris(2,2,6,6-tetramethyl-3,5-heptanedionato) lanthanum (La(TMHD) 3 Because the ligands for the La and Zr precursors could not be oxidized with O 2 or water at the deposition temperature, the samples used in this study were removed from the system and oxidized in a muffle furnace at 773 K for 5 min after each deposition cycle. Later studies showed that the ligands could be effectively oxidized at the deposition temperature using NO 2 as the oxidant and that identical growth rates for ZrO 2 on γ-Al 2 O 3 could be achieved by sequential dosing of the Zr(TMHD) 4 , precursor and NO 2 . As discussed in previous papers, 15,16 varying the exposure times and pressures did not affect deposition rates for the conditions used in these experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 79,130,152,180 ] In particular, the development of new electrode materials free from alkaline earth metal elements has received much attention. In the past two decades, many alkaline earth element-free metal oxides of different structures have been developed, such as perovskite, Ruddlesden-Popper, and spinel structures.…”
Section: Alkaline Earth Metal-element-free Composite Oxide Electrodesmentioning
confidence: 99%
“…While growth rates will depend on the precursor and surface, these are typically reported to be between 0.01 and 0.1 nm/cycle, values that correspond well to that which would be calculated based on the thickness of a precursor monolayer [28]. In apparent contradiction with this, two groups have reported growing ZrO 2 films in porous SOFC electrodes at rates between 0.5 and 0.6 nm/cycle [29,30]. Another group reported growing metallic W films at 0.4 nm/cycle, although the diameter of a W atom is only 0.25 nm [31].…”
Section: Problems With Conventional Ald Approaches To Catalyst and Elmentioning
confidence: 76%